Rheological properties and microscopic mechanism of rock asphalt composite modified asphalts. (26th April 2021) - Wen, Yankai; Guo, Naisheng; Wang, Lin; Jiao, Bozong; Li, Wei
Highlights: The blending effect of RACMA were assessed. The rheological properties and microstructure of RACMA were investigated. The RA/CRCMA exhibited better deformation resistance and temperature sensitivity. The RA/SBSCMA was a physical modification and the RA/CRCMA was a physical-chemical modification. Abstract: In order to improve the low temperature performance of rock asphalt modified asphalt, this work presents a laboratory study to evaluate the rheological properties of rock asphalt composite modified asphalts considering aging effect. The mechanical properties of rock asphalt (RA)/styrene–butadienestyrene (SBS) composite modified asphalt (RA/SBSCMA) and RA/crumb rubber (CR) composite modified asphalt (RA/CRCMA) were assessed based on penetration, softening point and rotational viscosity tests. Experiments, including bending beam rheometer (BBR), dynamic shear rheometer (DSR), multiple stress creep and recovery (MSCR), fluorescent microscope (FM), and Fourier transform infrared spectroscopy (FTIR), were conducted to investigate the rheological properties and microstructure of rock asphalt composite modified asphalts, as well as the effect of polymer modification and aging on asphalts. Results demonstrated that the RA/CRCMA exhibited higher consistency, better deformation resistance and temperature sensitivity than RA/SBSCMA. The performance grade (PG) of RA/CRCMA indicates superior high- and low-temperature performance, of which the RA/CRCMA with 5% rock asphalt and 18% crumb rubber (5R/18C) performed the best. The RTFO and PAV aging reduced the frequency sensitivity, facilitated the internal network structure stability and improved the compatibility of the RA/SBSCMA with 5% rock asphalt and 2% SBS (5R/2S). The 5R/18C presented superior compatibility in different aging states. The MSCR test results showed that the RA/CRCMA exhibits excellent resistance to permanent deformation and superior elasticity and recovery deformation ability. The FM test revealed that grooves and protrusions existed on the surface of RA/CRCMA, and the spheroidal RA particles and the CR particles with irregular linear or mesh structure dispersed in the asphalt phase separately. The FTIR test results proved that the RA/SBSCMA was a primarily physical modification in nature, while the RA/CRCMA was a physical–chemical modification. The CR presented stronger inhibition on the formation of carbonyl and sulfoxide compounds than the SBS resulting in more excellent anti-aging performance of corresponding composite modified asphalt. It is recommended that the optimal percentages of additive materials were 5% for RA and 18% for CR.